Perancangan Aplikasi Kata Lintas: Teka-teki Silang Dengan Menerapkan Aplikasi Fisher Yates - Ardiyansa, Fahmi (Jurnal Sains dan Teknologi Informasi, 2022)
Crossword puzzle is a word game which is usually in the form of a series of empty spaces in the form of black and white squares, the objective of this game is to fill the white boxes with letters, form certain words or phrases, by completing clues that lead to to a specific answer. The type of crossword puzzle game is currently developing, one of which is a cross word crossword puzzle, in this game the collection of letters is random and the user will look for a word from the random letters. However, it is still not known what randomization algorithm was used to make the crossword game application to scramble the letters so that they can become random letters that will be compiled by the user. After seeing some previous research, choosing the Fisher Yates Shuffle Algorithm which is applied using the Visual Basic Application as a solution is considered very appropriate, where this algorithm will initialize letters first to numbers then the initialized letters are randomized using an algorithm, and the user guesses the series of letters that are used has been scrambled before.